Environment-friendly recycled concrete and preparation method thereof
By modifying the surface of regenerated coarse aggregates with silicone modified acrylic resin, the shortcomings in strength and permeability of regenerated concrete are solved, and higher compressive strength and better permeability are achieved.
Patent Information
- Application Number
- CN202411870095.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-18
AI Technical Summary
Recycled concrete has shortcomings in strength and permeability, which makes it difficult for its compressive strength indicators to reach the level of ordinary concrete, and it is difficult to effectively prevent the invasion of liquid when facing water pressure.
Silicone modified acrylic resin is used to modify the regenerated coarse aggregate surface, seal the aggregate pores through physical action, and use the silicone segment to improve the hydrophobicity of the aggregate, thereby improving the permeability of the regenerated concrete. At the same time, the silicone group in the resin is hydrolyzed during concrete mixing and crosslinked with cement hydration products, enhancing the bonding strength of the regenerated coarse aggregate and the gelled material and improving the strength performance of the concrete.
Through the use of modified regenerated coarse aggregate, the permeability and strength properties of regenerated concrete are significantly improved, allowing it to more effectively resist water pressure and improve compressive strength.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the field of recycled concrete, and in particular to an environmentally friendly recycled concrete and a preparation method thereof. Background Art
[0002] Recycled concrete is a concrete made by partially or completely replacing natural aggregates with recycled aggregates formed by crushing and processing waste concrete. It has significant advantages in resource recycling, can reduce the pressure of construction waste on the environment and reduce the mining of natural aggregates.
[0003] However, recycled aggregates have many inherent defects. Their high porosity and the large number of cracks generated during the mechanical crushing process make the internal pore structure of recycled concrete complex and the connectivity enhanced after solidification, which greatly reduces the density. In terms of strength, due to the loose internal structure, its compressive strength index is difficult to reach the same level as ordinary concrete. In terms of impermeability, the presence of a large number of pores and cracks provides channels for liquid penetration, making it difficult to effectively prevent liquid intrusion when facing water pressure. Summary of the invention
[0004] In order to solve the deficiencies of recycled concrete in terms of strength and impermeability, the present application provides an environmentally friendly recycled concrete and a preparation method thereof.
[0005] In a first aspect, the present application provides an environmentally friendly recycled concrete, which includes the following components in parts by weight: 70-80 parts of cement, 20-30 parts of slag powder, 80-100 parts of modified recycled coarse aggregate, 120-150 parts of gravel, 120-150 parts of sand, 30-40 parts of water, 1-2 parts of water reducer; The surface of the modified recycled coarse aggregate is coated with an organosilicon-modified acrylic resin, and the raw materials of the organosilicon-modified acrylic resin include: hydroxyl acrylic resin, epoxy compounds with vinyl groups, and siloxane compounds with silicon hydrogen groups. The mass ratio of the hydroxyl acrylic resin, the epoxy compounds with vinyl groups, and the siloxane compounds with silicon hydrogen groups is 100:15-30:20-30.
[0006] In any of the above technical solutions, the preparation method of the organosilicon-modified acrylic resin is as follows: A hydroxy acrylic resin, an epoxy compound having a vinyl group and a double metal cyanide are mixed, and the temperature is raised to perform a ring-opening reaction to obtain a vinyl-terminated acrylic resin; A vinyl-terminated acrylic resin, a siloxane compound having a silyl hydrogen group and a platinum catalyst are mixed, and the temperature is raised to carry out a hydrosilylation reaction to obtain an organosilicon-modified acrylic resin.
[0007] In any of the above technical schemes, the ring-opening reaction is carried out in propylene glycol methyl ether, propylene glycol ethyl ether, propylene glycol butyl ether, propylene glycol methyl ether acetate, propylene glycol methyl ether propionate, propylene glycol ethyl ether propionate, ethylene glycol monoethyl ether acetate, diethylene glycol ethyl ether acetate, diethylene glycol butyl ether acetate, dipropylene glycol methyl ether, dipropylene glycol ethyl ether, dipropylene glycol butyl ether, dipropylene glycol dimethyl ether, dipropylene glycol diethyl ether, diethylene glycol ethyl ether acetate or diethylene glycol butyl ether acetate solvent.
[0008] In any of the above technical solutions, the epoxy compound having a vinyl group is selected from glycidyl methacrylate and / or allyl alcohol glycidyl ether.
[0009] In any of the above technical solutions, the siloxane compound having a silicon hydrogen group is one or a combination of trimethoxysilane, triethoxysilane, and methyldimethoxysilane.
[0010] In any of the above technical solutions, the mass percentage content of hydroxyl groups in the hydroxyl acrylic resin is 2 to 4%.
[0011] In any of the above technical solutions, the temperature of the ring-opening reaction is 105-120°C, and the temperature of the hydrosilylation reaction is 70-90°C.
[0012] The organosilicon-modified acrylic resin attached to the surface of the recycled coarse aggregate in the present application can, on the one hand, block the pores of the aggregate by physical action, and can also use its organosilicon segments to improve the hydrophobicity of the aggregate, thereby improving the impermeability of the recycled concrete. On the other hand, siloxane groups are introduced into the resin, which can be hydrolyzed to produce silanol groups during the concrete mixing process, and can cross-link with silanol groups in cement hydration products (such as calcium silicate gel), thereby enhancing the bonding strength between the recycled coarse aggregate and the cementitious material, and then improving the strength performance of the concrete. It can be seen that the organosilicon-modified acrylic resin in the present application can simultaneously improve the impermeability and strength performance of the recycled concrete.
[0013] It should be noted that in the preparation process of the above-mentioned organosilicon-modified acrylic resin, the hydroxy acrylic resin and the epoxy compound having a vinyl group are subjected to ring-opening polymerization under the catalysis of double metal cyanide, unsaturated vinyl groups are introduced into the acrylic resin, and then a hydrosilylation reaction is carried out with a siloxane compound having a silicon hydrogen group to obtain an acrylic resin having a siloxane group, thereby achieving crosslinking of the resin with cement hydration products.
[0014] In any of the above technical solutions, the components also include 0.1 to 0.5% by mass of cement hydroxycarboxylic acid or hydroxycarboxylate.
[0015] In any of the above technical solutions, the hydroxycarboxylic acid is selected from one or more of citric acid, gluconic acid and salicylic acid.
[0016] In any of the above technical solutions, the water reducer is a polycarboxylate water reducer.
[0017] The use of the above-mentioned organosilicon-modified acrylic resin will accelerate the crystallization and solidification process of cement hydration products, which is not conducive to the slow growth of crystals to form a stable and dense structure, and reduces the density and strength of concrete. To this end, the present application helps to alleviate the above-mentioned problems by adding the above-mentioned hydroxycarboxylic acid or hydroxycarboxylate.
[0018] In any of the above technical solutions, the slag powder has a fineness of 400 to 500 μm. 2 / kg, and the activity index is not less than 70% at 7 days.
[0019] In any of the above technical solutions, the gravel is made of continuously graded particles.
[0020] In any of the above technical solutions, the sand is medium sand in zone II with a fineness modulus of 2.3 to 3.0.
[0021] In any of the above technical solutions, the cement is silicate cement.
[0022] In any of the above technical solutions, the particle size of the modified recycled coarse aggregate is 5 to 31.5 mm.
[0023] In a second aspect, the present application provides a method for preparing environmentally friendly recycled concrete, which is obtained by uniformly mixing cement, slag powder, gravel, sand, modified recycled coarse aggregate, water and other raw materials according to any of the above-mentioned recycled concrete ratios.
[0024] In summary, this application has the following beneficial effects: The present application uses a silicone-modified acrylic resin containing a siloxane group to perform surface modification on the recycled coarse aggregate, which can give the recycled aggregate good hydrophobicity and reactivity, achieve a cross-linking reaction with the cementitious material, and effectively compensate for the loss of the anti-permeability and strength properties of the recycled concrete. DETAILED DESCRIPTION Preparation Example
[0025] Preparation Example 1 A modified recycled coarse aggregate is prepared according to the following steps: Silicone modified acrylic resin Step 1: Add 800 mL of propylene glycol methyl ether acetate and 1000 g of hydroxyl acrylic resin (hydroxyl content 3%) into a reactor, and introduce nitrogen to expel the air in the reactor. Then add 230 g of glycidyl methacrylate and 30 ppm of double metal cyanide (relative to the total amount of hydroxyl acrylic resin and glycidyl methacrylate) into the reactor, heat to 120°C, and perform ring-opening polymerization. After 8 hours, the reaction is completed, and the reaction product is passed into a rotary evaporator to remove propylene glycol methyl ether acetate and unreacted raw materials under reduced pressure to obtain a vinyl-terminated acrylic resin.
[0026] Step 2: Put the vinyl-terminated acrylic resin prepared above and 260g of trimethoxysilane into a reaction kettle, stir evenly, then add 50ppm of divinyltetramethylsiloxane-coordinated platinum catalyst (0.5% platinum content), heat to 80°C, react for 6h, cool after the reaction, and vacuum to remove unreacted trimethoxysilane to obtain a silicone-modified acrylic resin.
[0027] Preparation of modified recycled coarse aggregate Step 3: Mix 1000g of silicone-modified acrylic resin with 600g of ethylene glycol monoethyl ether acetate, stir for 30 minutes to obtain a resin solution, immerse the recycled coarse aggregate (5-20mm continuous grading) in the resin solution, soak for 3 minutes, filter and dry to obtain modified recycled coarse aggregate.
[0028] Preparation Example 2 A modified recycled coarse aggregate is prepared according to the following steps: Step 1: Add 800 mL of propylene glycol methyl ether acetate and 1000 g of hydroxyl acrylic resin (hydroxyl content 3%) into a reactor, and introduce nitrogen to expel the air in the reactor. Then add 180 g of allyl alcohol glycidyl ether and 30 ppm of double metal cyanide (relative to the total amount of hydroxyl acrylic resin and allyl alcohol glycidyl ether) into the reactor, heat to 115°C, and perform ring-opening polymerization. After 10 hours, the reaction is completed, and the reaction product is passed into a rotary evaporator to remove propylene glycol methyl ether acetate and unreacted raw materials under reduced pressure to obtain a vinyl-terminated acrylic resin.
[0029] Step 2: Put the vinyl-terminated acrylic resin prepared above and 200g of trimethoxysilane into a reaction kettle, stir evenly, then add 50ppm of divinyltetramethylsiloxane-coordinated platinum catalyst (0.5% platinum content), heat to 85°C, react for 5h, cool after the reaction, and vacuum to remove unreacted trimethoxysilane to obtain a silicone-modified acrylic resin.
[0030] Preparation of modified recycled coarse aggregate Step 3: Mix 1000g of silicone-modified acrylic resin with 600g of ethylene glycol monoethyl ether acetate, stir for 30 minutes to obtain a resin solution, immerse the recycled coarse aggregate (5-20mm continuous grading) in the resin solution, soak for 3 minutes, filter and dry to obtain modified recycled coarse aggregate.
[0031] Preparation Example 3 A modified recycled coarse aggregate is prepared according to the following steps: Step 1: Add 800 mL of propylene glycol methyl ether and 1000 g of hydroxyl acrylic resin (hydroxyl content 4%) into a reactor, and introduce nitrogen to expel the air in the reactor. Then add 290 g of glycidyl methacrylate and 30 ppm of double metal cyanide (relative to the total amount of hydroxyl acrylic resin and glycidyl methacrylate) into the reactor, heat to 120°C, and perform ring-opening polymerization. After 8 hours, the reaction is completed, and the reaction product is passed into a rotary evaporator to remove propylene glycol methyl ether and unreacted raw materials under reduced pressure to obtain a vinyl-terminated acrylic resin.
[0032] Step 2: Put the vinyl-terminated acrylic resin prepared above and 300g of methyldimethoxysilane into a reaction kettle, stir evenly, then add 50ppm of divinyltetramethylsiloxane-coordinated platinum catalyst (0.5% platinum content), heat to 80°C, react for 6h, cool after the reaction, and vacuum to remove unreacted methyldimethoxysilane to obtain a silicone-modified acrylic resin.
[0033] Preparation of modified recycled coarse aggregate Step 3: Mix 1000g of silicone-modified acrylic resin with 600g of ethylene glycol monoethyl ether acetate, stir for 30 minutes to obtain a resin solution, immerse the recycled coarse aggregate (5-20mm continuous grading) in the resin solution, soak for 3 minutes, filter and dry to obtain modified recycled coarse aggregate.
[0034] Preparation Example 4 A modified recycled coarse aggregate is different from Preparation Example 1 in that step 2 is not performed and step 3 is performed directly; and the vinyl terminated acrylic resin obtained in step 1 is a silicone modified acrylic resin.
[0035] Preparation Example 5 A modified recycled coarse aggregate is different from Preparation Example 1 in that the organosilicon-modified acrylic resin prepared in step 2 is replaced by a commercially available organosilicon-modified acrylic resin (acrylic resin SJ-804). Example
[0036] The cement used in the following embodiments and comparative examples is P.O42.5 cement; the stone is 5-20 mm continuous graded natural crushed stone with a mud content of 0.8%; the sand is zone II medium sand with a fineness modulus of 2.6; the slag powder is S95 grade slag powder with a fineness of 400-500 m2 / kg and a 7d activity index of 95%; the polycarboxylate water reducer is Sika® ViscoCrete®-530P polycarboxylate water reducer.
[0037] Example 1, an environmentally friendly recycled concrete, weigh 7.6 kg of cement, 2.4 kg of slag powder, 14.2 kg of stone, 9 kg of modified recycled coarse aggregate of Preparation Example 1, 13.6 kg of sand, 1.5 kg of polycarboxylic acid water reducer, 23 g of citric acid, and 3.6 kg of water, put them into a mixer, mix them evenly, and obtain the concrete.
[0038] Example 2, an environmentally friendly recycled concrete, weigh 7.0 kg of cement, 2.8 kg of slag powder, 12.5 kg of stone, 10 kg of modified recycled coarse aggregate of Preparation Example 2, 14.3 kg of sand, 1.6 kg of polycarboxylic acid water reducer, 35 g of citric acid, and 4.0 kg of water, put them into a mixer, mix them evenly, and obtain the concrete.
[0039] Example 3, an environmentally friendly recycled concrete, weigh 8.0 kg of cement, 2.0 kg of slag powder, 14.6 kg of stone, 8 kg of modified recycled coarse aggregate of Preparation Example 3, 12.5 kg of sand, 1.2 kg of polycarboxylic acid water reducer, 10 g of sodium citrate, and 3.5 kg of water, put them into a mixer, mix them evenly, and obtain the concrete.
[0040] Example 4 is an environmentally friendly recycled concrete, which differs from Example 1 in that citric acid is not added. Comparative Example
[0041] Comparative Example 1 is an environmentally friendly recycled concrete, which differs from Example 1 in that the modified recycled coarse aggregate of Preparation Example 1 is replaced by an equal amount of the modified recycled coarse aggregate of Preparation Example 4.
[0042] Comparative Example 2 is an environmentally friendly recycled concrete, which differs from Example 1 in that the modified recycled coarse aggregate of Preparation Example 1 is replaced by an equal amount of the modified recycled coarse aggregate of Preparation Example 5. Performance testing
[0043] Test 1: According to the requirements of GB / T 17671-2021 Cement mortar strength test method (ISO method), the 7d compressive strength and 28d compressive strength of recycled concrete were measured. The arithmetic mean of the compressive strength of the six specimens was calculated as the average compressive strength of the group of specimens.
[0044] Test 2: According to the "Water Penetration Resistance Test - Water Penetration Height Method" in GB / T 50082-2009, the penetration height of the concrete specimen is tested to characterize the water resistance of the recycled concrete. During the test, the water pressure is generally controlled to be constant at 1.2±0.05MPa. The test is stopped after 24 hours. The specimen is taken out and split into two halves along the longitudinal section. After the water mark is clearly visible, the water mark is traced with ink, which is the water seepage outline. Then, the water seepage height of ten lines is measured with a trapezoidal glass plate, accurate to 1mm. The arithmetic mean of the water seepage height at the ten measuring points is taken as the water seepage height of the specimen, and then the arithmetic mean of the water seepage height of the six specimens is calculated as the average water seepage height of the group of specimens.
[0045] Table 1. Test results
[0046] Results analysis: Compared with Comparative Examples 1 to 2 using commercially available or ungrafted silicone-modified acrylic resins, Examples 1 to 4 using the silicone-modified acrylic resins of the present application have higher compressive strength and smaller penetration heights, indicating that Examples 1 to 4 are more excellent in both strength and impermeability. The reason may be that the siloxane groups in the silicone-modified acrylic resins of the present application can generate silanol groups after hydrolysis, and react with the silanol groups of cement hydration products to crosslink, thereby improving the strength and density of the recycled coarse aggregate and the internal structure of concrete; in addition, the siloxane-silicon chains formed by the reaction have good hydrophobicity, which helps to improve the impermeability.
[0047] Compared with Examples 1 to 3, the recycled concrete of Example 4 has outstanding initial strength (7d compressive strength), but poor later strength (28d compressive strength) and impermeability. The reason may be that the siloxane groups in the organosilicon-modified acrylic resin accelerate the crystallization and solidification of the hydration products in the early stage of hydration, which is not conducive to the formation of a dense and stable crystal structure, and may induce the formation of temperature cracks, resulting in the above consequences. The hydroxypropionic acid or hydroxypropionic acid salt added in Examples 1 to 3 can inhibit the acceleration effect of the modified resin through steric hindrance and / or electrostatic action.
[0048] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. An environmentally friendly recycled concrete, characterized in that: The composition comprises the following components in parts by weight: 70-80 parts of cement, 20-30 parts of slag powder, 80-100 parts of modified recycled coarse aggregate, 120-150 parts of gravel, 120-150 parts of sand, 30-40 parts of water, 1-2 parts of water reducer; The surface of the modified recycled coarse aggregate is coated with an organosilicon-modified acrylic resin, and the raw materials of the organosilicon-modified acrylic resin include: hydroxyl acrylic resin, epoxy compounds with vinyl groups, and siloxane compounds with silicon hydrogen groups. The mass ratio of the hydroxyl acrylic resin, the epoxy compounds with vinyl groups, and the siloxane compounds with silicon hydrogen groups is 100:15-30:20-30.
2. The concrete according to claim 1, characterized in that The preparation method of the organosilicon-modified acrylic resin is as follows: A hydroxy acrylic resin, an epoxy compound having a vinyl group and a double metal cyanide are mixed, and the temperature is raised to perform a ring-opening reaction to obtain a vinyl-terminated acrylic resin; A vinyl-terminated acrylic resin, a siloxane compound having a silane group and a platinum catalyst are mixed, and the temperature is raised to carry out a hydrosilylation reaction to obtain an organosilicon-modified acrylic resin.
3. The concrete according to claim 1, characterized in that The epoxy compound having a vinyl group is selected from glycidyl methacrylate and / or allyl alcohol glycidyl ether.
4. The concrete according to claim 1, characterized in that The siloxane compound having a silicon hydrogen group is one or a combination of trimethoxysilane, triethoxysilane and methyldimethoxysilane.
5. The concrete according to claim 1, characterized in that The mass percentage content of hydroxyl group in the hydroxyl acrylic resin is 2-4%.
6. The concrete according to claim 2, characterized in that: The temperature of the ring-opening reaction is 105-120°C, and the temperature of the hydrosilylation reaction is 70-90°C.
7. The concrete according to claim 1, characterized in that The components also include 0.1-0.5% cement mass of hydroxycarboxylic acid or hydroxycarboxylate.
8. The concrete according to claim 1, characterized in that The water reducer is a polycarboxylate water reducer.
9. The concrete according to claim 1, characterized in that The slag powder fineness is 400-500m 2 / kg, and the activity index is not less than 70% at 7 days.
10. A method for preparing environmentally friendly recycled concrete, characterized in that: According to the mix ratio of any one of claims 1 to 9, cement, slag powder, gravel, sand, modified recycled coarse aggregate, water and other raw materials are uniformly mixed to obtain the recycled concrete.
Citation Information
Patent Citations
Recycled aggregate self-compacting concrete and preparation method thereof
CN114436601A
Recycled aggregate concrete and preparation method thereof
CN116120009A
Recycled aggregate treating agent, preparation method thereof and concrete
CN117383853A
Recycled aggregate concrete and preparation method thereof
CN118724518A
Filler laminate for concrete structure, and concrete structure
JP2024071915A